Pulmonary aspergillomata: an assessment of clinical outcome after surgical resection and of the most immune response to aspergillus infection at cellular level - Lichtenberg, Wilhelm S A (Not Specified, 2025)
A pulmonary aspergilloma, one of the forms of pulmonary disease caused by the ubiquitous fungus Aspergil/us species, is a secondary fungal infection imposed on pre-existing pulmonary disease. It is commonly associated with haemoptysis, which may be life-threatening 8•9•12•17- 19 •30. Colonisation of pre-existing cavities due to previous infection with mycobacterium tuberculosis is well described 1•2. In South Africa, due to the high incidence of pulmonary tuberculosis 73, pulmonary aspergillomata are frequently encountered.